Impact of Managerial Reputation and Risk-Taking on Enterprise Innovation Investment From the Perspective of Social Capital: Evidence From China - Wang, Shuang; Zhao, Shukuan; Shao, Dong; Fan, Xueyuan; Zhang, Bochen (Frontiers in Psychology, 2022)
China's enterprises established in the emerging economy are relatively short of technological innovation resources, therefore these enterprises need to make use of managerial reputation to break through organizational boundaries in order to obtain richer social capital and reshape their technological creativity to cope with the complex and changeable international economic situation. This corporate phenomenon also serves as the key for China's economy to advance to the stage of high-quality development. Based on the panel data of Chinese A-share listed companies from 2007 to 2016, this paper adopts the Heckman two-stage evaluation model to empirically study the impact of managerial reputation on enterprise innovation activities, the moderating role of corporate governance, and the mediating role of risk-taking. From the standpoint of social capital, the findings indicate that managerial reputation promotes enterprise innovation investment. The mechanism test reveals that this correlation is realized through the mediating role of risk-taking. Furthermore, the promotion effect of management reputation on enterprise innovation investment is stronger when the enterprises adopt the CEO duality, the larger board size, higher management ownership, and stronger equity restriction. The conclusions of this study confirm the important role of social capital for enterprise innovation in the context of the Chinese economy. The study implications also enrich and expand the research on the influencing factors of enterprise innovation investment that focus on the managerial reputation and provide important business inspiration for enterprises to build reputation management strategy and promote the transformation and upgrading of local enterprises.